2017
DOI: 10.1080/09638288.2017.1362708
|View full text |Cite
|
Sign up to set email alerts
|

Situationally influenced tinnitus coping strategies: a mixed methods approach

Abstract: tinnitus coping strategies: A mixed methods approach AbstractPurpose The primary aim of this study was to identify coping strategies used to manage problematic tinnitus situations. A secondary aim was to determine whether different approaches were related to the level of tinnitus distress, anxiety, depression and insomnia experienced. Results There were 240 participants (137 males, 103 females), with an average age of 48.16 years (SD: 22.70). Qualitative content analysis identified eight problematic tinnitus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 52 publications
3
36
0
3
Order By: Relevance
“…From a rehabilitation perspective, understanding how tinnitus is experienced and dealt with is important. Avoidance behaviours and catastrophic thinking about tinnitus have, for instance, been associated with greater tinnitus severity and emotional distress . If negative and catastrophic thinking results in greater emotional distress, positive thoughts may be one way of breaking this cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a rehabilitation perspective, understanding how tinnitus is experienced and dealt with is important. Avoidance behaviours and catastrophic thinking about tinnitus have, for instance, been associated with greater tinnitus severity and emotional distress . If negative and catastrophic thinking results in greater emotional distress, positive thoughts may be one way of breaking this cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance behaviours and catastrophic thinking about tinnitus have, for instance, been associated with greater tinnitus severity and emotional distress. 17,18 If negative and catastrophic thinking results in greater emotional distress, positive thoughts may be one way of breaking this cycle. Thought and behaviour modification are important components of tinnitus management, and identifying how to promote these modifications is of value.…”
mentioning
confidence: 99%
“…This has also been reported by Thorén et al (2014) for participants undertaking an online rehabilitative intervention for hearing aid users. In the context of a tinnitus intervention, this is an important outcome as avoidance behaviours are often associated with increased tinnitus distress (Beukes et al 2017a;Hesser and Andersson 2009;Kleinstäuber et al 2013). The strategies provided helped participants with general problem solving and the management of stress and anxiety.…”
Section: Intervention Effectsmentioning
confidence: 99%
“…To meet the demand for tinnitus services, a deeper understanding of the difficulties those with tinnitus are facing is required (Hall et al 2018). Beukes et al (2017a) identified the main difficulties those with tinnitus face e.g. difficulty sleeping, listening and concentrating.…”
Section: Introductionmentioning
confidence: 99%
“…Some withdraw and limit going to places they believe will worsen their tinnitus. This approach is often associated with greater distress and poorer long-term outcomes (Beukes et al, 2017a;Hayes, Wilson, Gifford, Follette, and Strosahl, 1996). Those with tinnitus often do not realise that there are ways to cope, despite having tinnitus.…”
Section: Introductionmentioning
confidence: 99%